2019
DOI: 10.1111/bjh.16088
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 mutation subtypes impact response and survival outcomes in patients with Waldenström macroglobulinaemia treated with ibrutinib

Abstract: Summary Ibrutinib is associated with response rate of 90% and median progression‐free survival (PFS) in excess of 5 years in Waldenström macroglobulinaemia (WM) patients. CXCR4 mutations are detected in 30–40% of patients with WM and associate with lower rates of response and shorter PFS to ibrutinib therapy. Both frameshift (CXCR4FS) and nonsense (CXCR4NS) CXCR4 mutations have been described. The impact of these mutations on outcomes to ibrutinib have not been evaluated in WM patients. We studied consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 29 publications
7
61
1
1
Order By: Relevance
“…All 17 CXCR4 heterozygous mutations identified so far in WM span in the C-ter of the receptor, and closely resemble the already documented germline mutations of CXCR4 C-ter occurring in heterozygosis in WHIM syndrome [9]. Although their relevance for clinical presentation and overall survival, as well as their relationship with resistance to chemotherapy are still unsolved issues [26][27][28], several studies reported that patients with CXCR4 mutations present a significantly lower rate of adenopathy, and those with CXCR4 nonsense mutations have an increased BM disease burden, serum IgM levels, and/or risk of symptomatic hyperviscosity [29]. Moreover, Plerixafor inhibition of CXCL12/CXCR4 axis can reverse the tumor-promoting signals of stromal cells, increasing the spontaneous apoptosis rate of tumor cells and enhancing their response to chemotherapy [30,31].…”
Section: Waldenstrom's Macroglobulinaemiasupporting
confidence: 69%
“…All 17 CXCR4 heterozygous mutations identified so far in WM span in the C-ter of the receptor, and closely resemble the already documented germline mutations of CXCR4 C-ter occurring in heterozygosis in WHIM syndrome [9]. Although their relevance for clinical presentation and overall survival, as well as their relationship with resistance to chemotherapy are still unsolved issues [26][27][28], several studies reported that patients with CXCR4 mutations present a significantly lower rate of adenopathy, and those with CXCR4 nonsense mutations have an increased BM disease burden, serum IgM levels, and/or risk of symptomatic hyperviscosity [29]. Moreover, Plerixafor inhibition of CXCL12/CXCR4 axis can reverse the tumor-promoting signals of stromal cells, increasing the spontaneous apoptosis rate of tumor cells and enhancing their response to chemotherapy [30,31].…”
Section: Waldenstrom's Macroglobulinaemiasupporting
confidence: 69%
“…In 20% to 40% of patients, lymphoplasmacytes have somatic activating mutations in the C-terminal domain of the C-X-C chemokine receptor type 4 (CXCR4) gene, 10, 16 which are similar to germline mutations observed in WHIM syndrome (CXCR4 WHIM ). These heterogeneous mutations may be either truncating or frameshift, with potentially different clinical effect, 17 but are not helpful for WM diagnosis.…”
Section: Diagnosismentioning
confidence: 99%
“…5,10,11 CXCR4 mutations also confer both in vitro and clinical resistance to ibrutinib, particularly nonsense variants such as CXCR4 S338X . [10][11][12][13][14][15][16] In WM patients, CXCR4 S338X constitutes the most common CXCR4 mutation identified. 3,5 CXCR4 S338X is primarily subclonal to mutated MYD88, but shows a highly variable clonal distribution.…”
Section: Introductionmentioning
confidence: 99%